2011
DOI: 10.12741/ebrasilis.v4i3.154
|View full text |Cite
|
Sign up to set email alerts
|

Ovis aries (Artiodactyla: Bovidae) e Capra hircus (Artiodactyla: Bovidae) parasitados por Oestrus ovis (Diptera: Oestridae) no Distrito Federal, Brasil

Abstract: A oestrose é uma miíase obrigatória e cavitária de ovinos e caprinos, domésticos e selvagens, causada por larvas da mosca Oestrus ovis (Linnaeus). Este estudo relata a presença de O. ovis na região Centro-Oeste do Brasil como parasitas de caprinos e ovinos. Nós obtivemos seis larvas de ovinos e caprinos suspeitos de oestrose em Brasília. As larvas originaram duas moscas fêmeas adultas de O. ovis, após 20 e 23 dias respectivamente. Este achado está provavelmente associado à expansão e diversificação da agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
2
0
5
Order By: Relevance
“…This hypothesis is supported by Cansi et al (2011), Schenkel et al (2012 and Silva et al (2012b), who diagnosed the presence of sheep bot flies for the first time in the Federal District (central-western region of Brazil) and in the States of Mato Grosso and São Paulo (central-western and southeastern regions, respectively).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This hypothesis is supported by Cansi et al (2011), Schenkel et al (2012 and Silva et al (2012b), who diagnosed the presence of sheep bot flies for the first time in the Federal District (central-western region of Brazil) and in the States of Mato Grosso and São Paulo (central-western and southeastern regions, respectively).…”
Section: Discussionmentioning
confidence: 81%
“…In the State of Santa Catarina, southern region of Brazil sheep bot flies were also diagnosed, but it is worth noting that when average temperatures fell below 9.8 °C (49.64 °F), no O. ovis larvae were detected in the animals (RAMOS et al, 2006). Studies conducted by Cansi et al (2011), Schenkel et al (2012 and Silva et al (2012aSilva et al ( , 2013 reported presence of this parasite in the States of Goiás, Mato Grosso and São Paulo (central-western, central-western and southeastern regions of Brazil, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…No Nordeste, até o momento, não havia relatos de oestrose em ovinos e caprinos. No Brasil, a oestrose é comumente descrita nas regiões Sul e Sudeste, e ultimamente no Distrito Federal e Estado de Mato Grosso (Ribeiro 2007, Cansi et al 2011, Schenkel et al 2012). Os surtos de oestrose neste trabalho ocorreram em todas as estações do ano, em períodos secos e chuvosos, no entanto, no Sul do Brasil, ocorre com maior expressão na primavera e verão (Ribeiro et al 1990, Ramos et al 2006.…”
Section: Discussionunclassified
“…A obtenção da mosca de O. ovis foi realizada em temperatura ambiental laboratorial permitindo o desenvolvimento de estágios de vida livre da mosca, diferente do descrito por Cansi et al (2011), que obteve a pupa e o imago em condições controladas de temperatura e umidade, em 20-23 dias. Hall & Wall (1995) relataram que o desenvolvimento de L3 para pupa, dependerá apenas de condições climáticas e da estação do ano, confirmando a adaptabilidade e o desenvolvimento em condições ambientais específi-cas.…”
Section: Discussionunclassified
See 1 more Smart Citation